Management Of Human Resources In The Improvement Of Teacher Performance (Study On Mts Sunan Ampel Sumberkima Bali) - Imam Hidayat; Ahsin Daroini (Universitas Islam Kadiri, 2020)
This study discusses human resources in improving teacher performance which are specified into three aspects, namely: first to understand human resources at MTs Sunan Ampel Sumberkima Bali. Second, to influence the performance of teachers at MTs Sunan Ampel Sumberkima Bali. The third resource is to study human resource management at MTs Sunan Ampel Sumberkima Bali. The results of this study are expected to help in further research and are expected to provide input and advice in improving the quality of teacher work in educating the nation's next generation. This research was conducted at MTs Sunan Ampel Sumberkima Bali as one of the Islamic-based schools or madrassas on the island of Bali. The research method used is descriptive qualitative method with data collection methods by conducting observations, interviews, and documentation. The instruments used were observation guides, interview guides, and documentation formats. Data processing and analysis techniques are carried out by means of data reduction, data presentation, verification and conclusions, as well as testing the validity. The results showed that the existing human resources at MTs Sunan Ampel Sumberkima Bali can be categorized both in terms of acquisition and quality. Teacher performance is quite good by looking at the activities carried out. The implementation of human resource management implemented by the school principal at MTs Sunan Ampel Sumberkima Bali was carried out quite well.